2021
DOI: 10.1039/d1sc02042k
|View full text |Cite
|
Sign up to set email alerts
|

Molecular design of thermally activated delayed fluorescent emitters for narrowband orange–red OLEDs boosted by a cyano-functionalization strategy

Abstract: The establishment of simple molecular design strategy to realize red-shifted emission while maintaining good color purity for multi-resonance induced thermally activated delayed fluorescent (MR-TADF) materials remains an appealing yet challenging...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
128
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(148 citation statements)
references
References 43 publications
7
128
0
Order By: Relevance
“…By the virtue of MR effect induced by the exquisite combination of boron, nitrogen, and sulfur atoms, the radiative decay rate constant (k r ) of BSBS-N1 in the doped film was calculated to be as high as 9.0 10 7 s À1 , which is comparable to those of other reported MR-TADF materials. [8][9][10][11][12][13][14][15] Moreover, BSBS-N1 was found to exhibit a notably high RISC rate constant (k RISC ) of 1.9 10 6 s À1 , which is reasonably consistent with the foregoing short exciton life-time and large F d /F p ratio. To the best of our knowledge, this k RISC is the highest ever reported value among the MR-TADF materials (typically k RISC % 10 3 -10 5 s À1 ; 2.0 10 5 s À1 for n-DABNA), [9] suggesting an enhanced SOC between the associated excited states with different spin multiplicities governing the RISC.…”
supporting
confidence: 68%
“…By the virtue of MR effect induced by the exquisite combination of boron, nitrogen, and sulfur atoms, the radiative decay rate constant (k r ) of BSBS-N1 in the doped film was calculated to be as high as 9.0 10 7 s À1 , which is comparable to those of other reported MR-TADF materials. [8][9][10][11][12][13][14][15] Moreover, BSBS-N1 was found to exhibit a notably high RISC rate constant (k RISC ) of 1.9 10 6 s À1 , which is reasonably consistent with the foregoing short exciton life-time and large F d /F p ratio. To the best of our knowledge, this k RISC is the highest ever reported value among the MR-TADF materials (typically k RISC % 10 3 -10 5 s À1 ; 2.0 10 5 s À1 for n-DABNA), [9] suggesting an enhanced SOC between the associated excited states with different spin multiplicities governing the RISC.…”
supporting
confidence: 68%
“…In 2021 Bin et al reported that the attachment of a cyano (CN) functionality at the LUMO position of the MR-TADF skeleton can promote attractive red-shifted emission due to the exceptional electronwithdrawing capacity of the CN group, which represents the first example of orange-red MR-TADF emitters. [43] Meanwhile, the linear CN group adopts a coplanar conformation with the MR-framework to restrict structure relaxation associated with rotation, which is beneficial to maintain a small full-width at half-maximum. With the support of high PLQY (90 %) and high radiative of 2.2 × 10 7 s À 1 , an excellent EQE of 33.7 % was recorded with a narrow FWHM below 50 nm.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…More recently, led by the pioneering work by Hatakeyama et al in 2016, [5] a new paradigm of TADF emitters featuring the multi-resonance (MR) effect has emerged and attracted immense interest with the astonishing potential for overcoming the aforementioned drawbacks of D-A-structured TADF systems. [5][6][7][8][9][10][11][12][13][14][15] In the design of so-called MR-TADF molecules, as represented by the renowned DABNA analogs, a triphenylborane core is planarized and stabilized [16] by connecting with nitrogen atoms (amine moieties) to construct a rigid polycyclic aromatic framework, giving rise to opposite resonance effects by the mutually ortho-disposed boron and nitrogen atoms. [5,6] This electronic feature enables the resulting polycyclic molecules to have an alternating (atomically separated) HOMO/LUMO pattern, with a small DE ST and large Frank-Condon overlap integral, and hence exhibit efficient narrowband TADF.…”
mentioning
confidence: 99%